Bees and birds in aegean epiphanic dance (Mantichora. Italian Journal of Performance Studies, 2020)
Epiphanic dance was one of the principal aspects of ritual performance in the Aegean Bronze Age. The pictorial evidence from seals, seal impressions, wall paintings, and other works shows (mostly) women dancing, usually in open-air settings, to induce divine apparitions or to engender such visions in their audiences. The present study proposes that the hive dances of the honey bee and the aerial acrobatics of the barn swallow served as models for costumes and choreography, whose memory may well be preserved on Homer’s shield of Achilles, with its dancing space that “Daedalus made at Knossos for Ariadne” (Iliad 18:590-606).